(untitled) (Communications in Computational Physics, 2020)
We present a new lattice Boltzmann formulation for elastic solids and analyse the issue of conservation laws for solids. This new formulation allows tunable Poisson ratio. As a first benchmark problem, we consider an elastic wave propagating in an infinite homogeneous medium with point force and point dipole Ricker wavelet as the source. The method is successful in simulating behavior of elastic wave motion as a function of Poisson ratio.